A Study on Self-Development Practices During Covid-19 - A.Manojkumar; Prasanth (PT FORMOSA CENDEKIA GLOBAL, 2022)
Self-Development or Personal development is a lifelong process. Self-development practices are those activities that develops a person's capabilities and build human capital and potential, facilitate employability, enhances quality of life, the realization of dreams and aspirations. The study on self-development practices during covid-19 deals with the perspective of how students effectively used their lockdown period towards their self-development skills. This research is done with the help of primary data collection. As an emerging management student, this study has provided an opportunity to understand about how students from different business school spent their valuable time during this pandemic.